Switchable Optically Active Schottky Barrier in La0.7Sr0.3MnO3/BaTiO3/ITO Ferroelectric Tunnel Junction. (13th May 2021) - Rivera‐Calzada, Alberto; Gallego, Fernando; Kalcheim, Yoav; Salev, Pavel; del Valle, Javier; Tenreiro, Isabel; León, Carlos; Santamaría, Jacobo; Schuller, Ivan K.
Abstract: One of the most desirable attributes of non‐volatile memories and memristors is a fast and non‐destructive read out of their resistive state. Prototypical ferroelectric (FE) memories use the bulk photovoltaic response associated to the polarization of FE films to address this requirement by optically sensing binary memory cells. A more advanced type of non‐volatile memories is FE tunnel junctions (FTJs). They feature resistive state ratios R High / R Low up to 10 6, with a continuum of resistive states accessible, making them promising candidates for neuromorphic computing applications. A novel approach is presented to achieve the optical sensing of the resistive state in a La0.7 Sr0.3 MnO3 /BaTiO3 /ITO FTJ, by using the Schottky barrier forming in the La0.7 Sr0.3 MnO3 /BaTiO3 interface to dramatically enhance the optical response of the 5 nm BaTiO3 (BTO) barrier. Illumination with UV light exceeding the BTO bandgap through the top transparent ITO electrode generates a photovoltaic response in the R High state, with an open circuit voltage V oc of 400 mV at 20 K, enabling the optical sensing of the resistive state. In the R Low state, the Schottky barrier is removed and the photoresponse disappears. Abstract : The optical sensing of the resistive state of a ferroelectric tunnel junction is presented using the Schottky barrier forming in the bottom interface, La0.7 Sr0.3 MnO3 /BaTiO3, to dramatically enhance the barrier optical response. The UV illumination through a top transparent ITO electrode generates a solid photovoltaic response in the high resistance state that disappears in the low resistance state.